Tatalaksana oleh Petugas Kesehatan dan Faktor Risiko Terjadinya Kegagalan Perawatan di Rumah terhadap Penderita Pnemonia Balita - Ichwanu Kusno, Djauhar Ismail, Haripurnomo Kushadiwijaya (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Pneumonia kills approximately 4 million babies and infants in the world each year. In Indonesia, it was estimated that 450.000 infant deaths occur every year that estimated was caused by infection of acute respiratory tract (ISPA) especially pneu-monia. Since" 199411995, TTS regency has implemented P2ISPA (acute respiratory tract infection control program), yet pneumonia in children under five years old remain the main problem. Problem is aspects of management of health personnel and home care are considered as risk factor of recovering for pneumonia sufferer.Objectives: This study is devided into 2 stages, Stage I case study (evaluation pro-gram) that aimed at examining management of application program by health person-nel. Stage II was observasional study with cohort design that aimed at examining risk factors of the failure of care at home of infant morbidiy due to pnemonia.Methods: Subjects of this study in stage I were health center workers and stage II children between 2 month-5 years old who suffered from pneumonia in Kapan and Nulle health center area. Data was collected by observation and measurement with data analysis of table 2x2Results and conclusions: The result of this study showed that the management is not with appropriate the standard management. Factors that had significant effect on re-covery of pneumonia patiens included mothers who don't have enough knowledge about pneumonia (RR=5,06; p = 0,0054), innappropriate at home (RR=3,87; p =0,0006), innapropriate medicine consumption (RR=2,54; p=0,019) and low quality of home care (RR=3,20; and p = 0,006).There for it is suggested to the patient to have a qualified AR1 management, information improvement and home visit to improve the recovery. Keywords: recovery, management and care at home, pneumonia.